Novel Immunomodulatory Proteins Generated via Directed Evolution of Variant IgSF Domains - Levin, Steven D.; Evans, Lawrence S.; Bort, Susan; Rickel, Erika; Lewis, Katherine E.; Wu, Rebecca P.; Hoover, Joseph; MacNeil, Sean; La, David; Wolfson, Martin F.; Rixon, Mark W.; Dillon, Stacey R.; et al. (Frontiers in Immunology, 2020)
Immunoglobulin superfamily member (IgSF) proteins play a significant role in regulating immune responses with surface expression on all immune cell subsets, making the IgSF an attractive family of proteins for therapeutic targeting in human diseases. We have developed a directed evolution platform capable of engineering IgSF domains to increase affinities for cognate ligands and/or introduce binding to non-cognate ligands. Using this scientific platform, ICOSL domains have been derived with enhanced binding to ICOS and with additional high-affinity binding to the non-cognate receptor, CD28. Fc-fusion proteins containing these engineered ICOSL domains significantly attenuate T cell activation in vitro and in vivo and can inhibit development of inflammatory diseases in mouse models. We also present evidence that engineered ICOSL domains can be formatted to selectively provide costimulatory signals to augment T cell responses. Our scientific platform thus provides a system for developing therapeutic protein candidates with selective biological impact for treatments of a wide array of human disorders including cancer and autoimmune/inflammatory diseases.